Effekter av predationsrisk på sånglärkors (Alauda arvensis) habitatval på åkermark - Ehlin, Johanna (2010)

(untitled)
Along with other European farmland birds, the skylark (Alauda arvensis) has declined rapidly since the 1970’s. Between 1975 and 2003, the Swedish population of skylarks declined with 64 %.